Place of Colistin-Rifampicin Association in the Treatment of Multidrug-Resistant Acinetobacter Baumannii Meningitis: A Case Study - Dahraoui Souhail; Belefquih Bouchra; Badia Belarj; Rar Laila; Frikh Mohammed; Oumarou Mamane Nassirou; Ibrahimi Azeddine; Charki Haimeur; Abdelhay Lemnouer; Mostafa Elouennass (Case Reports in Infectious Diseases)
Treatment of Acinetobacter baumannii meningitis is an important challenge due to the accumulation of resistance of this bacteria and low meningeal diffusion of several antimicrobial requiring use of an antimicrobial effective combination to eradicate these species. We report a case of Acinetobacter baumannii multidrug-resistant nosocomial meningitis which was successfully treated with intravenous and intrathecal colistin associated with rifampicin.